Sosialisasi Pengenalan Barang Berbahaya Bagi Siswa SMK - Wynd Rizaldy; Lis Lesmini; Aisyah Rahmawati; Ika Utami Yulihapsari; Intan Maesti Gani (Greenation Publisher & Yayasan Global Resarch National, 2024)
Abstract : Although socialization of the risk of hazardous materials has been carried out in every area and mode of transportation that stores and transports these goods, both on signs and labels, it is still found that many people need to be more familiar with the potential dangers. Initial understanding of Hazardous Materials Identification was provided to students of Darul Ma'arif Logistic Vocational High School (SMK) located in North Jakarta as a Community Service (PKM) activity. This was done due to the lack of knowledge about the potential dangers of hazardous materials. Therefore to transform knowledge, the socialization method was carried out face-to-face. The aim of this PKM is to improve the knowledge and skills of SMK students in handling hazardous materials safely. The results of the pretest and posttest showed an increase in the final understanding of the participants by 17 points from 40 participants, with a high category of 0.718 in N Gain, and this socialization was declared quite effective with a Gain % of 71.8%.